2015
DOI: 10.1589/jpts.27.451
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chest expansion resistance exercise in chronic stroke patients: a randomized controlled trial

Abstract: [Purpose] The aim of this study was to examine the initial effects of chest expansion resistance exercise (CERE) applied to chronic stroke patients on their pulmonary functions, chest expansion, and functional gait ability. [Subjects] Forty chronic stroke patients without any respiration-related rehabilitation program experience (21 men and 19 women; times elapsed since occurrence of stroke: 21.8 ± 5.3 months) were randomly and equally allocated to a CERE group (experimental group) and a control group. [Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Another study of inspiration and expiration breathing exercise methods that aimed to improve the pulmonary function of patients with cervical spinal cord injuries showed that the expiration exercise group had significantly higher pulmonary function in all evaluation indexes (except for FEV 1 /FVC) than the inspiration exercise group 19 ) . The present study showed more significant differences in the BMIG, which is likely to be related to increased chest wall expansion 20 , 21 ) . It also showed that the change in FVC was significantly increased in the BMIG as compared to the BMEG, whereas the change in CEV was significantly decreased in the BMIG as compared to the BMEG.…”
Section: Discussionsupporting
confidence: 44%
“…Another study of inspiration and expiration breathing exercise methods that aimed to improve the pulmonary function of patients with cervical spinal cord injuries showed that the expiration exercise group had significantly higher pulmonary function in all evaluation indexes (except for FEV 1 /FVC) than the inspiration exercise group 19 ) . The present study showed more significant differences in the BMIG, which is likely to be related to increased chest wall expansion 20 , 21 ) . It also showed that the change in FVC was significantly increased in the BMIG as compared to the BMEG, whereas the change in CEV was significantly decreased in the BMIG as compared to the BMEG.…”
Section: Discussionsupporting
confidence: 44%
“…Kim et al in their study on chronic stroke patients proved that CERE improved chest expansion attributing the changes to facilitation of respiration causing increased inflow of air into the lungs. However, pulmonary function test results (FEV1, FVC, vital capacity) did not show any significant changes [30]. In another study performed on elderly, Kim et al documented a significant change in chest expansion and inspiratory muscles strength following 6 weeks of CERE wherein the elderly participants showed an improvement of 48% in chest expansion and 25% in MIP values [17].…”
Section: Discussionmentioning
confidence: 94%
“… Kim et al (2015) reported that 40 patients with hemiplegia due to stroke were treated with the concept-based respiratory muscle exercises of proprioceptive neuromuscular facilitation in an EG. 6MWT was compared within-group and between-groups, and showed significant improvement.…”
Section: Discussionmentioning
confidence: 99%